2015
DOI: 10.1007/s00170-014-6780-9
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal forming of the large-size AZ80A magnesium alloy forging with high mechanical properties

Abstract: There is an increasing demand for magnesium alloy in the automobile and aerospace industries, but the large-size magnesium alloy forging is difficult to be obtained by conventionally machining with high mechanical properties. The isothermal forming was carried out to form the large-size magnesium alloy forging. The forming process of isothermal forming is studied by finite element model simulation and experiment. The microstructure and tensile properties of the magnesium alloy forging processed by isothermal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The absence of studies discussing such parts is easily visible throughout this review. While some authors conduct T5 treatments [33,91,138] and others have shown the increase of material ductility after recrystallization treatment [32,75], there are nearly no forged parts in T6 state mentioned in the investigated literature [75,99]. This might be the case because only few Mg alloys exist which show age hardening to a strength beyond that gained by work hardening in the forging process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of studies discussing such parts is easily visible throughout this review. While some authors conduct T5 treatments [33,91,138] and others have shown the increase of material ductility after recrystallization treatment [32,75], there are nearly no forged parts in T6 state mentioned in the investigated literature [75,99]. This might be the case because only few Mg alloys exist which show age hardening to a strength beyond that gained by work hardening in the forging process.…”
Section: Discussionmentioning
confidence: 99%
“…A wheel-shaped part (Ø 630 mm) was produced by Yuan et al [91] by isothermal die forging. The forming process was simulated first and based on the simulation data, forging took place at 330 • C using a speed of 1 mm s −1 .…”
Section: Az80mentioning
confidence: 99%
“…With the continuous development of precision plastic forming technology, the requirements of the hot forging process in the metal products industry are increasingly becoming stricter. Light weight and safety have become important standards for assessing the quality of metal forging products [1][2][3][4]. Magnesium alloy is a new type of metal material with extensive development potential and has the advantages of light weight, high specific strength and stiffness, good dimensional stability, easy processing, and recycling ability [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of the as-forged properties of AZ80 forged components in recent years has become more widespread in literature. Many studies have focused on the characterization of the monotonic structural properties of forged AZ80 Mg, in open die forgings [3,4] as well as for closed die forged components such as wheels [5][6][7], aerospace components [7][8][9][10], and finally, automotive structural components [11][12][13][14][15][16][17][18][19][20]. In general, the main focus of these studies was the feasibility of achieving adequate material flow to produce the desired forged shape, whilst characterizing the resulting microstructure and quasi-static material properties.…”
Section: Introductionmentioning
confidence: 99%